Un argumento sobre su excepción: acerca del travestismo de Eva Perón en la pieza teatral de Copi - Pron, Patricio (Anales de Literatura Hispanoamericana, 2008)
The purpose of this work is to discuss the character of performance and staging of Eva Perón’s figure as it is presented in two texts of the Argentinian literature: Copi’s play Eva Perón (1970) and Jorge Luis Borges’ short story “El simulacro” (1960). The frequent appearance of a cross-dressed actor as the main character of the play is not based on the assumed fact that this would be part of the so called “anti-Peronist mythologization”, as it had usually been done before, but on the importance of crossdressed characters in Copi’s work, as the author intends to demonstrate in an extensive approach of his narrative work.